2022
DOI: 10.1097/cnd.0000000000000426
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Symptom Burden of Charcot–Marie–Tooth Disease Type 1A: Findings From an Observational Digital Lifestyle Study

Abstract: Objectives:This study aims to explore the impact of Charcot-Marie-Tooth disease type 1A (CMT1A) and its treatment on patients in European (France, Germany, Italy, Spain, and the United Kingdom) and US real-world practice. Methods:Adults with CMT1A (n ¼ 937) were recruited to an ongoing observational study exploring the impact of CMT. Data were collected via CMT&Me, an app through which participants completed patientreported outcome measures. Results:Symptoms ranked with highest importance were weakness in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
(31 reference statements)
0
3
0
2
Order By: Relevance
“…Pain is a well-studied and significant comorbid condition accompanying CMT. [2][3][4][5] Due to inadequate relief from standard pain treatments, individuals with CMT may seek alternatives, such as cannabis. However this has not been previously investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain is a well-studied and significant comorbid condition accompanying CMT. [2][3][4][5] Due to inadequate relief from standard pain treatments, individuals with CMT may seek alternatives, such as cannabis. However this has not been previously investigated.…”
Section: Discussionmentioning
confidence: 99%
“…3 Complications of CMT include sleep apnea, restless legs syndrome, daytime sleepiness, and impaired sleep. 4 Although there is no known cure for this slowly progressive disease, there are treatments such as physical and occupational therapy, orthotics, and pharmacotherapies to manage symptoms. The medications used for pain management are varied and included aspirin, nonsteroidal anti-inflammatory medications, acetaminophen, tricyclic antidepressants, anticonvulsants, and opioids.…”
Section: Introductionmentioning
confidence: 99%
“…Isso parece demonstrar que o comprometimento clínico dos pacientes do presente estudo não tem como fator agravante os aspectos sociais, como nível de escolaridade e renda. Diferentemente de outras doenças crônicas progressivas, como a DMD, que exige cuidado integral e intensivo, com alto custo financeiro, 6 a CMT possui uma condição de progressão lenta que exige menores custos, que envolvem medidas como o tratamento de reabilitação. A respeito da escolaridade, talvez a distribuição em diferentes grupos tenha influenciado a análise estatística, portanto, na análise final, com o aumento do número amostral, iremos definir novos grupos, em busca de reduzir esse possível viés.…”
Section: Discussionunclassified
“…E acarretam em dificuldades nos usos dos membros, maior fraqueza muscular, assim como fadiga e dor, comprometendo a qualidade de vida. 6 Quanto as limitações podemos citar que apesar da CMT ser considerada uma doença rara, o número de participantes foi pequeno, e que é necessário a investigação de fatores que afetam tanto a gravidade da doença, quanto a força.…”
Section: Discussionunclassified
“…The combination of these symptoms causes in patients an altered gait associated with difficulty in balance (10)(11)(12)(13). It has also been shown that patients with CMT have anxiety and depression problems (14) with alteration of body composition (15) and low levels of physical activity (PA) (14,(16)(17)(18). A sedentary lifestyle increases body weight, muscle loss, and musculoskeletal pain, worsening the medical case of patients with CMT (19); this condition increases the risk of comorbidities such as metabolic syndrome or cardiovascular disease (20).…”
Section: Introductionmentioning
confidence: 99%